Lowland rice soils in Malaya : - Kawaguchi, Keizaburo (The center for Southeast Asian studies, 1969)
Contents: Introduction; methods; samples; pedological characteristics of sample soils; general chemical and physical characteristics; fertili characteristics; mineralogical characteristics.